2002
DOI: 10.18388/abp.2002_3757
|View full text |Cite
|
Sign up to set email alerts
|

IGF-I: from diagnostic to triple-helix gene therapy of solid tumors.

Abstract: Alterations in the expression of growth factors and their receptors are associated with the growth and development of human tumors. One such growth factor is IGF-I (insulin-like growth factor I ), a 70-amino-acid polypeptide expressed in many tissues, including brain. IGF-I is also expressed at high levels in some nervous system-derived tumors, especially in glioblastoma. When using IGF-I as a diagnostic marker, 17 different tumors are considered as expressing the IGF-I gene. Malignant glioma, the most common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…The critical role that the IGF axis plays in the growth of GBM has been well documented in various experimental models (6,22,23). In early studies, the IGFs were shown to enhance 3D growth of glioblastoma (21) and more recently, high IGF-IR expression levels were identified as an independent prognostic factor associated with shorter survival, a poorer response to temozolomide (4) and resistance to anti-EGFR (24) and anti-PDGFR (25) treatments in GBM patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The critical role that the IGF axis plays in the growth of GBM has been well documented in various experimental models (6,22,23). In early studies, the IGFs were shown to enhance 3D growth of glioblastoma (21) and more recently, high IGF-IR expression levels were identified as an independent prognostic factor associated with shorter survival, a poorer response to temozolomide (4) and resistance to anti-EGFR (24) and anti-PDGFR (25) treatments in GBM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, C6 cells may have become apoptotic if their IGF-IR expression levels were below the threshold required for survival, or entered cell cycle arrest if they expressed the requisite receptor levels for survival but not for cell cycle entry. A variable response of the tumor microenvironment to tumor cells with different IGF-IR expression levels may also have contributed to the divergent outcomes, as IGF-IR signaling levels were shown to affect tumor cell immunogenicity (23,34).…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that anti-gene cell therapy, giving comparable results to those of currently applied chemotherapy, inhibitors or antibodies [72] [73] [85], could be used either alone [57] [86] or as combined therapies i.e. antisense targeting simultaneously different elements of growth factors signalling pathway [49] [91], including study of control CD8 (+) T-cell effect or functions [92], new tools of cell transfection [93] and especially the search for new onco-proteins [94] and growth factor targets [14] [50] [65] [95] [96] appear as the near future challenge. Among growth factors, targeting IGF-I system in relation with cancer therapy constitutes ongoing basic and clinical research [97]- [99]; the IGF-I being considered as one of the principal precancerous markers [3] [100] [101], has conducted to experiments on suppression of IGF-I expression in tumors, following directly by immuno-gene therapy of malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Such antisense technology is being developed to target the growing list of oncogenes and local growth factors that have been identified in the development of HCC [19,24]. Targets being that have been examined include the FGF-2, IGF-I, VEGF-2, and COX-2 genes [29][30][31]. Use of these techniques has shown antitumor effects in vitro and in animal models.…”
Section: Gene Therapymentioning
confidence: 99%